Offer Document Disclosures and its Impact on Equity Return in India (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Primary market investors deploy their surplus funds inequity issues on the basis of disclosures made by the issuer companies in their offer documents. An attempt has been made in the present study to measure the impact of offer document disclosures regarding turnover, total assets, net worth, earnings per share, book value, percentage of dividend paid, age, promoters stake in post-issue capital and issue size on equity return in India. Taking a sample of 97 equity issues of the size of Rs. 10 crore or more of closely held unlisted companies belonging to 5 different industries during a period of 12 years from 1992-93 to 2003-04 and after applying Linear Multiple Regression Analysis, the study finds that the offer document disclosures covered by the study explained significant amount of variation in equity return in case of issues of banking as well as finance and investment industry. Disclosure of turnover in case of issues of finance and investment industry and of net worth and earnings per share in case of issues ofpharmaceutical industry establishedits statistically significant impact on equity return during the period covered by the study. The industry-wise performancerevealed that the equity issues of banking industry proved more beneficial for long-term investors whereas the issues of IT industry remained more profitable for short-term investors. The study reported that the equity issuesof finance and investment industryprovided less initial return and highest negative return to the investors after three years from first trading day of the issues on Bombay Stock Exchange